Free‐Standing Carbon Nanofibrous Films Prepared by a Fast Microwave‐Assisted Synthesis Process. (11th November 2013) - Schwenke, Almut M.; Stumpf, Steffi; Hoeppener, Stephanie; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> Carbon nanofibrous (CNF) films are of great interest for various applications, e.g., as substrates for electrodes, sensors, or catalysts. Here, a fast microwave‐assisted synthesis is reported to fabricate square‐centimeter large free‐standing carbon nanofibrous films of approximately 10 μm thickness utilizing nickel‐based catalysts and ethanol as carbon source. The obtained CNF coatings exhibit a good stability and partial self‐delamination from the substrate is observed, which enables their easy detachment from the substrate without the need for further treatment. Scanning electron microscopy is applied to investigate the morphology of the films and to develop a growth model.